DIGITAL TRANSFORMATION IN EDUCATION: IMPLEMENTING AI-BASED LEARNING SYSTEMS IN BATAM - Eryc, Eryc; Valentinus, Sefryanto; Herman, Herman (ISTEK WIDURI, 2025)
Digital transformation has become a global phenomenon of reshaping education. In developed countries, Artificial Intelligence (AI) is widely used to enhance learning outcomes, while in Indonesia adoption remains limited due to infrastructural and digital literacy constraints. This study investigates the impact of AI usage, attitudes toward AI, and implementation challenges on student engagement and task quality at Monte Sienna School, Batam. A mixed-method approach was applied, combining quantitative analysis using Structural Equation Modeling (SEM-PLS) with qualitative insights from teacher interviews. Findings reveal that attitudes toward AI significantly influence both student engagement and task quality, while AI usage alone does not directly improve academic performance. Challenges related to data security and identity authenticity remain weak and inconsistent, reflecting local infrastructural and cultural limitations. This study contributes empirical evidence from the Indonesian school context and highlights the importance of teacher guidance, digital literacy, and policy support in maximizing AI’s potential in education.